PENERAPAN TERAPI HIPNOSIS LIMA JARI DAN AROMATERAPI MAWAR PADA PASIEN KECEMASAN AKIBAT HIPERTENSI - Dwika Dwika Yulian Nur Ihsan; Iwan Somantri; Ridwan Kustiawan (Poltekkes Kemenkes Tasikmalaya, 2026)
ABSTRACT Background : Anxiety is one of the most common psychological disorders, frequently found in patients with hypertension. Anxiety can trigger increased blood pressure and worsen the patient's condition. Non-pharmacological approaches such as five-finger hypnosis therapy and rose aromatherapy are alternative methods to help reduce anxiety without side effects. Objective: This study aims to describe the nursing care process, the implementation of five-finger hypnosis therapy and rose aromatherapy, and to evaluate anxiety responses in two hypertensive patients with anxiety symptoms. Methodology: This research used a qualitative method with a comparative case study design involving two clients experiencing hypertension accompanied by anxiety. The intervention was carried out over five consecutive days, with observation of changes in anxiety scores before and after therapy. Results: Assessment results showed that both clients experienced a decrease in anxiety levels from moderate to mild after receiving the combination therapy. Additionally, the clients demonstrated improved emotional regulation and stress response.